Co-precipitation method for the preparation of nanocrystalline ferroelectric SrBi2Nb2O9 ceramics - Gaikwad, S. P.; Dhage, S. R.; Potdar, H. S.; Samuel, V.; Ravi, V. (Journal of Electroceramics, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase SrBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Sr2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was found while heating powder at 850 C and pure SrBi2Nb2O9 (SBN) phase was formed as revealed by the X-ray diffraction (XRD) studies. Particle size and morphology was studied by transmission electron microscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic materials; ferroelectricity; Oxides